2004
DOI: 10.1161/01.cir.0000105701.98663.d4
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cardiac Overexpression of Endothelin-1 Induces Inflammation and Dilated Cardiomyopathy in Mice

Abstract: Background-Myocardial expression of endothelin-1 (ET-1) and its receptors ET A and ET B is increased in heart failure.However, the role of ET-1 and its signaling pathways in the pathogenesis of myocardial diseases is unclear. Methods and Results-Human ET-1 cDNA was placed downstream of a promoter responsive to a doxycycline (DOX)-regulated transcriptional activator (tTA). This line (ET ϩ ) was bred with one harboring cardiac myocyterestricted expression of tTA (␣MHC-tTA). Myocardial ET-1 peptide levels were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 47 publications
7
113
1
4
Order By: Relevance
“…Similar characteristics of cardiomyopathy such as significantly lower LV pressure and dP/dt max were also found in mice overexpressing ET-1 orthotopically in cardiomyocytes (4). This led to the hypothesis that ET-1 might be an important mediator of doxorubicin cardiotoxicity.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Similar characteristics of cardiomyopathy such as significantly lower LV pressure and dP/dt max were also found in mice overexpressing ET-1 orthotopically in cardiomyocytes (4). This led to the hypothesis that ET-1 might be an important mediator of doxorubicin cardiotoxicity.…”
Section: Discussionmentioning
confidence: 53%
“…However, the results of these studies were neutral in terms of mortality and symptoms (24), leading to an intense discussion on whether the use of receptor subtype-specific endothelin receptor blockers may be of advantage. Interestingly, the above cited study by Yang and coworkers showed that the combined ET A /ET B antagonist LU420627, but not the selective ET A antagonist LU135252, prolonged the survival of ET-1-overexpressing cardiomyopathic mice (4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it has been proposed that ETA, the prevalent receptor subtype in the cardiac tissue, mediates the main cellular functions of endothelin, whereas ETB is involved in the clearance of ET-1. However, since ET-3 also evokes a hypertrophic response [7] and the pathogenic effects of conditional, myocyte-specific ET-1 overexpression are delayed by a mixed ETA/ETB antagonist but not an ETA-selective antagonist [8], ETB also plays an important functional role in adult cardiac ventricular myocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In congestive heart failure, NGF levels in the heart decrease (21) as plasma norepinephrine levels rise; concomitantly, ET-1 plasma levels rise as well (22), although it is not clear how these changes are interrelated. Additionally, a recent report suggests that ET-1 overexpression in the adult mouse heart leads to a dilated cardiomyopathy and death (23). Given the developmental role of ET-1 in regulating NGF production by cardiac myocytes, evaluation of similar actions in the adult heart, and secondary effects on sympathetic function, may be warranted.…”
Section: Figurementioning
confidence: 99%